Peran Pemerintah dalam Pengembangan Teluk Berdiri sebagai Objek Ekowisata di Kabupaten Kuburaya Kalimantan Barat - Heriyanto; Debbie Yuari Siallagan; Sulaiman (EDUTOURISM Journal Of Tourism Research, 2020)
This study aims to determine the role of government in the development of the Teluk Berdiri ecotourism as well as to determine the efforts that can be made to develop the ecotourism. The research method used in this research is descriptive qualitative method with the aim to make a description, a systematic, factual and accurate description of the facts investigated. The instrument used was a survey sheet and interview guidelines. The data analysis technique uses triaggulation technique, which is a technique for checking the validity of data that utilizes something different outside the data for the need to check the comparison of the same data from other sources. The results showed that the interest of tourists is still a local tourist, this is due to a number of factors such as inadequate facilities and infrastructure, such as lack of accessibility, lack of promotion, and others. The role of the government is currently trying to provide support, one of which is improving road access to the tour. Furthermore, efforts that can be made by the government are establishing cooperation with the local community for the construction of facilities and infrastructure, improving accessibility and promoting local wisdom and traditions to attract visitors. The development of environment-based tourism or ecotourism can be a guide in making use of the tourism sector and can be used as an attraction of an area to increase regional income (PAD).